Exploring EFL Students’ Writing Difficulties: from Dimensions to Errors - Dyah Ayu Nugraheni; Dihliza Basya (FKIP Universitas Islam Jember, 2018)
The present study aimed to explore the students’ writing difficulties examined from the five dimensions and common errors faced by students in Essay Writing Course. Descriptive research with explanatory design was employed in this study to investigate the students’ writing difficulties which are analyzed from writing score and the sentence constructions in their cause-effect essay writing. This study purposively sampled 25 fourth semester students who join the Essay Writing Course. Essay Writing Tests (EWT) is used to get the data of students’ writing. The results of data collection were in the forms of students’ writing scores compared from each dimension (content, organization, grammar, vocabulary, and mechanics) and error analysis based on the word and sentential levels. The errors analyzed, then, were classified into error types. The results yielded that students’ writing dimensions are between 2-3 points based on the scoring rubric which means they are still in basic and below basic writers. In addition, the most error types analyzed covered capitalization, punctuation, sentence fragments, spelling, subject-verb agreement, run-on sentences as literal translation from Indonesian, word choices, nouns, preposition, verbs, adjective, articles, word order, verb tense, passive voice, possessive (‘s), and transition words. The result of study could be a basic data for the English teachers/lecturers to know the students’ writing difficulties thoroughly from each dimension of writing and error types and further to assist them to write better. Keywords: writing difficulties, dimensions of writing, error analysis, essay writing